2010
DOI: 10.1111/j.1467-7652.2010.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Only half the transcriptomic differences between resistant genetically modified and conventional rice are associated with the transgene

Abstract: SummaryBesides the intended effects that give a genetically modified (GM) plant the desired trait, unintended differences between GM and non-GM comparable plants may also occur. Profiling technologies allow their identification, and a number of examples demonstrating that unintended effects are limited and diverse have recently been reported. Both from the food safety aspect and for research purposes, it is important to discern unintended changes produced by the transgene and its expression from those that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 57 publications
2
46
0
1
Order By: Relevance
“…Rice Montero et al (2010) found around 0.40% transcriptomic differences in leaves of in vitro-grown experimental rice (Oryza sativa) lines producing an antifungal protein. They could distinguish differences due to transgene insertion (15%), transgene expression (50%), and regeneration (35%).…”
Section: Peamentioning
confidence: 99%
“…Rice Montero et al (2010) found around 0.40% transcriptomic differences in leaves of in vitro-grown experimental rice (Oryza sativa) lines producing an antifungal protein. They could distinguish differences due to transgene insertion (15%), transgene expression (50%), and regeneration (35%).…”
Section: Peamentioning
confidence: 99%
“…Using transcriptomics, (Montero et al, 2011) compared the conventional rice var. Senia to the transgenic variant Senia-afp constitutively expressing the AFP antifungal protein.…”
Section: Results From Omics Experimentsmentioning
confidence: 99%
“…Four studies (Batista et al, 2008;Luo et al, 2009;Montero et al, 2011;Xue et al, 2012) compared transgenic rice to wild type rice.…”
Section: Effect Of Transgene On Transcriptomics Difference Between Gmmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major classes of compounds, part of the nonenzymatic antioxidant system, playing an important role in least, in the experiments focused on identifying the differences between genetically modified plants and their original counterparts, as part of the risk assessment strategy, an important percentage of the dissimilarities observed are caused by the in vitro procedure (Montero et al, 2011;Fonseca et al, 2015).…”
Section: Introductionmentioning
confidence: 99%